2009
DOI: 10.1097/wnf.0b013e31816d1cdc
|View full text |Cite
|
Sign up to set email alerts
|

Trazodone for the Treatment of Sexual Dysfunction Induced by Serotonin Reuptake Inhibitors

Abstract: The 5-HT2 antagonist, trazodone, may be beneficial in the management of SSRI-induced sexual dysfunction. Large-scale, placebo-controlled, double-blind studies with 5-HT2 antagonists are required to substantiate these preliminary observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 14 publications
1
20
0
1
Order By: Relevance
“…In a pilot study, it was observed that trazodone may be beneficial in the management of selective serotonin-reuptake inhibitor-induced sexual dysfunction (Stryjer et al, 2009). In men with ED and a degree of psychogenic component sufficient to reduce the efficacy of medical management, a combination of trazodone with sildenafil gave promising results in a pilot study (Taneja, 2007).…”
Section: Drugs For Nonintracavernosal Administrationmentioning
confidence: 99%
“…In a pilot study, it was observed that trazodone may be beneficial in the management of selective serotonin-reuptake inhibitor-induced sexual dysfunction (Stryjer et al, 2009). In men with ED and a degree of psychogenic component sufficient to reduce the efficacy of medical management, a combination of trazodone with sildenafil gave promising results in a pilot study (Taneja, 2007).…”
Section: Drugs For Nonintracavernosal Administrationmentioning
confidence: 99%
“…For men taking an SSRI, 20 mg of tadalafil has been shown to significantly improve erectile function, with tolerable side effects [44]. Trazodone has also proven to be effective in treating ED in men taking SSRIs [45]. …”
Section: Resultsmentioning
confidence: 99%
“…Specific differences in men and women were improvement in erectile performance in men and lubrication in women. No correlations were noted between clinical improvement of depression or anxiety and improvement in sexual dysfunction [Stryjer et al 2009]. …”
Section: Discussionmentioning
confidence: 99%